Sterigmatocystin in foodstuffs: higher concern due to climate changes - Viegas, Susana (2018)
The Food and Agriculture Organization of the United Nations (FAO) estimated that approximately 25% of the cereals produced in the world are contaminated with mycotoxins. There are many factors involved in mycotoxins production by fungi but the climate is the most important. The climate of some countries will probably become warmer reaching temperatures of 33 ºC, which is, for instance, a temperature very close to the optimal for several mycotoxins production. This is the case of sterigmatocystin (STC), produced mainly by Aspergillus versicolor. Although its toxicity is lower than AFB1, STC is classified as being carcinogenic classified by IARC as group 2B, with immunomodulatory activity, mutagenicity in mammalian cells after metabolic activation, inhibition of the cell cycle and mitosis, and an increase in the formation of reactive oxygen species and lipid peroxidation in vivo. This review intended to collect information present in scientific papers about STC presence in foodstuffs and an exhaustive search was made for papers from January 2010 available on online scientific databases. Papers reported the occurrence of STC in basic daily foods at low levels such as wheat, rye, corn, barley and by-products, bread, soy, groundnuts, rice, cocoa beans, vegetables and pistachio, and at high levels in red pepper, caraway, cumin (18-23 μg.kg-1) and coffee beans (12 000 μg.kg-1). Although in most of the foods the levels found are low, there is still a concern since it can lead to a chronic exposure that, in some countries, can result in higher exposure to the presence in several foodstuffs. So, further studies are needed in order to assess exposure considering different diet regimes. Additionally, research projects should be dedicated to understanding if the contamination by STC in different crops and products is expected to increase due to climate change. This will allow recognizing the most suitable measures to avoid contamination and prevent consumers exposure.